PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURALNUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWAKELAS VII.6 SMP NEGERI 20PEKANBARU - Handayani, Regina Handayani; Saragih, Sehatta Saragih; Hutapea, Nahor Murani Hutapea Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The background of this research is a learning process and mathematics learning outcomes are not optimal in the class VII.6 Junior High School 20 Pekanbaru in the even semester academic years 2013/2014. The research was classroom action research to improve learning process andmathematics learning outcomeswith applied the cooperative learning Numbered Head Together structural approach. There are 40 students in the class, consist of 17 boys and 23 girls.This research consist of two cycles, and at the end of every cycle carried out mathematics learning outcomes test. The instrument of data collection on this research are observation sheets mathematics learning outcomestests. Analysis data of observation was performed with narrative descriptive analysis and analysis data of mathematics learning outcomeswas performed with descriptive statistical analysis. Result of this research showed an increase in students from the base score (62,5%) to 65% on the first test and 80% on the second test. Results of this research indicates that the cooperative learning Numbered Head Together structural approachcan improve learning process and studentsmathematics learning outcomes class VII.6Junior High School20 Pekanbaru. Key Word : Mathematics Learning Outcome, Cooperative Learning Model Structural Approach of Numbered Head Together, Class Action Research